Field notes and letter to Thomas H. Kent contributed by Pam Allen and Reid I. Allen, December 2, 1997 - Allen, Pamet al; Allen, Reid I.et al (1997)
Fall report of birds and locations contributed by Pam Allen and Reid I. Allen. Also included is a letter from Pam Allen to Thomas H. Kent regarding fall bird sightings. This item was used as supporting documentation for the Iowa Ornithologists' Union Quarterly field report of fall 1997. Epson - sheet feed